MicroRNA‐21 increases the expression level of occludin through regulating ROCK1 in prevention of intestinal barrier dysfunction. Issue 3 (9th October 2018) - Liu, Zhihua; Li, Chao; Chen, Shihua; Lin, Hongcheng; Zhao, Huan; Liu, Min; Weng, Jinsheng; Liu, Ting; Li, Xiaomei; Lei, Chao; Li, Chen; Jiang, Yanqiong; et al.
Abstract: Objective: The aim of this study is to investigate the role of molecular mechanism of microRNA (miR)‐21 on tight junction (TJ)‐proteins and its protective effects on the intestinal barrier. Methods: TJ proteins and target genes expression were analyzed in miR‐21 inhibition and overexpression NCM460 cell lines. To further verify the role of miR‐21, the mmu‐miR‐21 intestinal epithelial conditional knockout (IKO) mice model was established. MiR‐21 expression was detected in clinical specimens of acute stercoral obstruction patients. Results: Rho‐associated protein kinase 1 (ROCK1) were identified as target genes of miR‐21. There is a negative correlation between miR‐21 expression level and TJ proteins levels. TJ protein and ROCK1 were significantly decreased in miR‐21 IKO mice, which presented intestinal inflammation response and intestinal barrier dysfunction (both P  < 0.05). Determination of clinical samples showed consistent results with NCM460 cell line and miR‐21 IKO mice. Conclusions: MiR‐21 could be a protective factor of intestinal barrier dysfunction, which promoting the expression of TJ protein by targeting ROCK1 in vivo and in vitro. Abstract : miR‐21 could also play an important role in the protection of intestinal barrier dysfunction. We constructed the miR‐21 intestinal conditional knockout (IKO) mice, which suffered from intestinal inflammation and intestinal epithelial injury. Clinical samples also supported the conclusion